EEG abnormalities and clinical phenotypes in pre-school children with autism spectrum disorder - Romero-González, Marina; Navas-Sánchez, Patricia; Marín-Gámez, Ester; Barbancho-Fernández, Miguel Ángel; Fernández Sánchez, Victoria Eugenia; Guzmán Parra, José; Lara-Muñoz, José Pablo (Elsevier, 2022)
Abnormalities on electroencephalography (EEG) results have been reported in a high percentage of children with Autism Spectrum Disorder (ASD). The purpose of this study was to explore the prevalence of EEG abnormalities in a clinical population of pre-school children with Autism Spectrum Disorder and the differences in terms of the following phenotypic characteristics: adaptive behavior, executive functioning, severity of Autism Spectrum Disorder core symptoms, and comorbidity symptoms.
Keywords: Niños autistas; Autism spectrum disorder; Clinical features; EEG abnormalities; Pre-school children